The Wearing of Dastar in Sikhism and Its Relation With the Amrit Sanskar Ceremony - Aman Daima, Md. Zain; Syed Mohd Hafiz, Syed Omar; Jaffary, Awang (2016)
In the religion of Sikh, wearing the turban or the dastar is a religious practice that is a symbolic proof of their faith to the Sikh Guru’s teachings and their holy book. The dastar carries its own distinguished characteristics in terms of the way it is worn, its measurements and colours. It completes the Sikh dresscode or uniform, known as Panch Kekaar or the 5Ks, that is an integral part of their identity. Nevertheless, not all Sikh followers wear the dastar. This depends on individual’s willingness to undergo a baptism ritual, known as the amrit sanskar. The dastar-wearing Sikhs who have requested for amrit are called amrit-dhari; they are true Sikh followers who adhere to the teachings of their Sikh teachers. One of the objectives of this study is to provide information to the multi-racial society in Malaysia, especially the Muslim society, concerning the wearing of dastar in Sikhism and its relation with baptism. Through this information, it is hoped that a society that is tolerance and have mutual respect for each other, irrespective of race and religion, as aspired by the concept of 1Malaysia, is borne. In this study, the textual analysis method is adopted to retrieve information on the dastar and the amrit sanskar ritual. In addition, various references in relation to the Sikh religion were also made.